Communication, language and expression body in physical education - Eliane Gomes da Silva; Lúcia Helena Ferraz Sant'Agostino (Universidade Federal de Santa Catarina, 2005)
This paper intends to give basis for understanding corporal expression as a language, which would enable the child to produce information/knowledge within the physical education. Based on the concepts of childhood, language and comunication, we understand that the phsysical education must promove the establishment of comunicative relationships, in which corporal expresion apears as a special manifestation. Based on Peirce Semiotics, the corporal expression is conceive as a language in itself, constitude by spontan gests, which ar produced by diversous stimuli. This enable the children to construct interpretating/interpretative relations in this signs fluxe, and, because of it, to produce knowledge.